Explaining seasonal patterns of food consumption - Spence, C (Elsevier, 2021)
When questioned, people typically report that different foods are appropriate at different times of the year. That is, patterns of food consumption exhibit seasonal variations. Changes in food odour hedonics and familiarity ratings have also been reported over the course of the year, especially in those countries with marked seasonal changes in climate. The question addressed in this review is what factors help to explain these seasonal differences in food consumption. While our nutritional needs undoubtedly do differ somewhat over the course of the year, environmental (e.g., think only of changes in ambient temperature and/or humidity), physiological/perceptual (i.e., threshold changes), and psychological factors (e.g., wanting to make a healthy start in the New Year) also play a role. Taken together, though, it would appear that cultural/ritual factors, as well as the influence of increasingly-sophisticated data-driven marketing may be more important than nutritional, environmental, or physiological factors in helping to explain why it is that so many of us choose to eat different foods at different times of the year, despite the increasing availability of many foods on a year-round basis in the increasingly globalized food marketplace in many developed countries.